PENERAPAN KMK (KEPUTUSAN MENTERI KESEHATAN)NO. HK.01.07-MENKES-1591-2020 DI LINGKUNGAN PUSKESMAS MEKARWANGI TANAH SAREAL KOTA BOGOR - Maisanggeni, Royyan Aziz; Fajri, Ibrahim (YUSTISI, 2020)
Coronavirus Disease 2019 (Covid 19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). In connection with the policy of controlling infectious disease outbreaks, Indonesia already has Law Number 4 of 1984 concerning Communicable Disease Outbreaks, Government Regulation Number 40 of 1991 concerning Management of Contagious Disease Outbreaks, and Regulation of the Minister of Health Number 1501 / Menkes / Per / X / 2010 concerning Certain Types of Infectious Diseases That Can Cause Outbreaks and Countermeasures. For this reason, in the context of efforts to prevent the Covid-19 epidemic early, Mekarwangi Community Health Center implements health protocols. This paper aims to examine how the application of health protocols for patients and health workers in the Mekarwangi Community Health Center to overcome the COVID-19 outbreak following the Decree of the Minister of Health (KMK) No. HK.01.07-MENKES-1591-2020. AbstrakCoronavirus Disease 2019 (Covid 19) adalah penyakit menular yang disebabkan oleh Severe Acute Respiratory Syndrome Coronavirus 2 (SARSCoV-2). Berkaitan dengan kebijakan penanggulangan wabah penyakit menular, Indonesia telah memiliki Undang – Undang Nomor 4 Tahun 1984 tentang Wabah Penyakit Menular, Peraturan Pemerintah Nomor 40 Tahun 1991 tentang Penanggulangan Wabah Penyakit Menular, dan Peraturan Menteri Kesehatan Nomor 1501/Menkes/Per/X/2010 tentang Jenis Penyakit Menular Tertentu Yang Dapat Menimbulkan Wabah dan Upaya Penanggulangan. Untuk itu dalam rangka upaya penanggulangan dini wabah covid – 19, Puskesmas Mekarwangi melakukan penerapan protokol kesehatan. Tulisan ini betujuan untuk mengkaji bagaimana Penerapan Protokol Kesehatan bagi pasien dan petugas kesehatan di lingkungan Puskesmas Mekarwangi dalam upaya penanggulangan wabah COVID-19 sesuai Keputusan Menteri Kesehatan (KMK) No. HK.01.07-MENKES-1591-2020.